PENCATATAN RESERVASI PADA FRONT OFFICE DEPARTMENT LABERSA GRAND HOTEL and CONVENTION CENTER - Romi Wahdiromodon; Siti Sofro Sidiq (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This research aims to determine about the procedure for reservations form of Front Office Department at Labersa Grand Hotel and Convention Center Pekanbaru. Reservation form is the process of making a list of guest orders in accordance with existing procedures. Labersa is an abbreviation of "Eight Brothers" which was inaugurated in 2009, Labersa Grand Hotel and Convention Center is located on the road Labersa - Parit Indah, Pekanbaru which is a subsidiary of PT. LABERSA HUTAHEAN. This research to make use qualitative method to analysis set of case, wich to become the key informan in this research as much as three people’s. That is 1  Duty Manager, 1 Reservation Staff and 1 Front Desk Agent. Sources were obtained through interview, observation, and documentation. Based on result of this research, the conckusions of this research ate reservation form of front office department has been done, but still needs to be improved raising required so that reservation form will be better in the future.  Keywords : Reservation form, Front Office, Hotel